The sense and meaning ascribed to professional work by women with cancer - Małgorzata Rębiałkowska-Stankiewicz (Nofer Institute of Occupational Medicine, 2021)
Background The fact that professional activity is reduced is a very challenging experience for persons with cancer whose sense of self-worth is linked to their work. Not only does cancer often become the reason for their deteriorated socio-economic position but it also reduces the quality of life assessment in cancer patients. Material and Methods The aim of the study was to discover the sense and meaning that women with cancer ascribe to their professional work. The research was carried out among 6 women diagnosed with cancer, aged 32-49 years. A qualitative research strategy was adopted in the study and interpretative phenomenological analysis was applied. Results Based on the conducted research, when faced with cancer, the respondents often perceive professional work as a factor that triggers cancer and, at the same time, one that can increase their self-esteem, giving meaning to their life. It, therefore, seems crucial to support the professional activity of cancer patients and to create jobs promoting health. Conclusions When working with a person suffering from cancer, it is worth considering the possibilities that returning to work is likely to carry. It is important to create such jobs and work environments that would be consistent with the concept of health promotion. It seems that the key factors here are the appointment of persons responsible for the return process of a person with a chronic illness, accompanied by efficient communication between the employer and occupational health services, and efficient exchange of information between the treating physician and the workplace (with the employee's consent). Med Pr. 2021;72(1):1-8